Dice thrown from the beginning? An empirical investigation of determinants of firm level growth expectations - Terjesen, Siri (Estudios de Economía, 2016)
This study investigates three competing but complementary perspectives on factors related to entrepreneurial firm growth. We examine individual (entrepreneur) firm and national environment factors associated with the growth expectations of nascent, baby and established firms. Using 25,384 data points from Global Entrepreneurship Monitor (GEM)’s survey of entrepreneurial activity in 35 countries, we find male gender, personal acquaintance with an entrepreneur, innovative product/service, low levels of competition and based in less-developed countries are associated with high growth expectations for all three business stages. Nascent and baby firms’ business growth expectations are also linked to having higher levels of start-up capital and outside investment. In contrast to some previous research, we find that a firm’s initial size is the best predictor of growth expectations. Altogether, size-related factors determine not only initial growth expectations, but also growth expectations at later firm stages. The law of disproportionate growth (i.e. a small number of firms are responsible for most expected job creation) holds for both start-ups and established businesses, although the latter are more rare. While both start-up and established firm growth expectations are higher in the developing countries, the fastest growing young firms are mainly found in developed countries.